1991
DOI: 10.1159/000138830
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pregnancy on Muscarinic Receptor Density and Function in the Rabbit Urinary Bladder

Abstract: The contractile response of the rabbit urinary bladder to field stimulation consists of both cholinergic and purinergic components. In general, approximately 60% of the contractile response to field stimulation is cholinergic and 40% is purinergic. Although the purinergic response represents a significant proportion of the initial (phasic) pressure response to field stimulation of the isolated whole bladder, it contributes only 10–15 % of the ability of field stimulation to empty the bladder. The current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…Despite no significant change in gravid bladder weight or in-vitro bladder capacity, pregnancy induced a 35% decrease in muscarinic receptor density, based on radioligand binding (34 fMol/mg vs 22), a 50% reduction in response to bethanechol, and a markedly increased response to ATP (16). Our data closely mirrors and reconfirms that pregnancy induces muscarinic receptor down regulation in the bladder, as well as in the uterus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Despite no significant change in gravid bladder weight or in-vitro bladder capacity, pregnancy induced a 35% decrease in muscarinic receptor density, based on radioligand binding (34 fMol/mg vs 22), a 50% reduction in response to bethanechol, and a markedly increased response to ATP (16). Our data closely mirrors and reconfirms that pregnancy induces muscarinic receptor down regulation in the bladder, as well as in the uterus.…”
Section: Discussionsupporting
confidence: 82%
“…In the pregnant human the bladder undergoes many functional changes, among them an increase in residual volume, decrease in bladder tone and increase in urinary stress incontinence. The decreases in muscarinic receptor density in both the rabbit bladder dome and base by 24% to 41%, and the previously detailed decreases in gravid bladder contractile response to bethanechol (16), help to explain these clinical findings.…”
Section: Gravid and Virgin Bladdersmentioning
confidence: 65%
“…Receptor binding studies in bladder tissue from pregnant animals revealed a significantly reduced muscarinic receptor density (50%), corresponding to the decrease in response to bethanechol of the whole bladder. The results were interpreted to mean that pregnancy induced an increase in the purinergic and a decrease in the cholinergic components of the urinary bladder response to field stimulation (Levin et al, 1991). A reduction of the muscarinic receptor density in the pregnant rabbit bladder was confirmed by other investigators (Baselli et al, 1999).…”
Section: Pharmacology Of the Lower Urinary Tractmentioning
confidence: 60%
“…Thus, in the presence of bethanechol, bladder strips from pregnant rabbits generated 50% less tension in response to calcium than those from nonpregnant rabbits (Zderic et al, 1990). The isolated whole bladder from pregnant animals responded to low-frequency stimulation and to ATP with a greater increase in intravesical pressure than did preparations from virgin rabbits, whereas the response to bethanechol was greater in the virgin rabbits (Levin et al, 1991). Receptor binding studies in bladder tissue from pregnant animals revealed a significantly reduced muscarinic receptor density (50%), corresponding to the decrease in response to bethanechol of the whole bladder.…”
Section: Pharmacology Of the Lower Urinary Tractmentioning
confidence: 89%
“…Estrogen administra tion has been shown to result in marked increases in a-adrenergic and muscarinic re ceptors [7], Pregnancy induces a significant decrease in the contractile response to musca rinic stimulation which has been correlated with a decrease in muscarinic receptors [8], In view of the marked effects of estrogen (and pregnancy) on autonomic receptor density, and the contractile response to autonomic agonists, it was appropriate to determine the actions of thyroid hormone on the response of the bladder to autonomic stimulation, and the density of autonomic receptors.…”
Section: Introductionmentioning
confidence: 99%